KINERJA BELT CONVEYOR PADA UNIT CRUSHING PLANT DI PT. NUR HAZANAH KARYA ABADI DISTRIK PRAFI KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Abdonsons F. Ongirwalu; Yulius G. Pangkung (INTAN Jurnal Penelitian Tambang, 2021)
Belt conveyor is an equipment used for transfering material that is widely used in the mining industry. The equipment consists of belts made of various types of materials that are resistant when transporting solid materials. The research aims to figure out the performance of the belt conveyor operated by PT. Nur Hazanah Karya Abadi, to determine the actual and theoretical production of a conveyor belt, and to determine the efficiency of a conveyor belt. The results show the theoretical productions of each belt conveyor fraction is as followed: fraction 1 at 94,396 tons/hour, fraction 2 at 97,164 tons/hour, fraction 3 at 211,566 tons/hour, and fraction 4 at 73,587 tons/hour. The actual productions of each conveyor belt fraction are as followed: fraction 1 at 23,617 tons/hour, fraction 2 at 28,185 tons/hour, fraction 3 at 30,307 tons/hour, and fraction 4 at 8,447 tons/hour. The value of work efficiency on the conveyor belt is 35%. The performance of belt conveyor in PT. Nur Hazanah Karya Abadi, based on the calculation of production and work efficiency, has not really good yet.